22 A Mixed-Method Study on Older Adults' Adherence to Home Exercise Programme: Patients' and Physiotherapists' Perspective. (20th December 2019) - Timmons, Suzanne; Aziz, Siti Khalijah Abdul
Abstract: Background: Regular exercise and physical activities have shown to be beneficial especially in older adults to maintain their function. To reap these benefits, recommended exercises need to be adhered to. However, there is lack of consistency in the literature on what is the degree of adherence to home exercise programmes (HEPs) among older adults. Objective: The purpose of this study was to explore factors affecting older adult patients' adherence to HEP prescribed to them and how HEP was perceived by both older adults and physiotherapists. Design: A mixed-method study design was used in this study Methods: 28 older adults attending outpatient physiotherapy clinic were given an exercise journal to record their adherence to HEP prescribed by their physiotherapists for six weeks. Subsequently, semi-structured interviews were conducted with seven older adults and five physiotherapists. The interviews were audio recorded and transcribed. After which, the interviews were analysed using content analysis. Results: 14 participants returned their exercise journal. The rate of adherence out of 42 days of HEP prescribed was 79.8% or 5.6 days per week. Only medium inverse correlation was found between risk of depression and HEP adherence. No significant correlation was found for cognitive function, self-efficacy to exercise, quality of life and mobility status. Four key themes consisting of perception to HEP, mode of delivery to HEP, barriers and facilitators of HEP adherence emerged from the data. Conclusion: Older adults' internal motivation is important to improve HEP adherence. External factors such as family support, companion while exercising, physiotherapists' support in terms of designing likeable and easy HEPs, investigating reasons for non- adherence, modifying exercises and education on importance of adherence to HEPs could affect HEP adherence of older adults. Additionally, having more community based exercise classes are factors that could potentially promote adherence.